Vigenère Cipher Algorithm Optimization for Digital Image Security using SHA512 - Riadi, Imam; Fadlil, Abdul; Tsani, Fahmi Auliya (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 13 No 2 (2022): Vol. 13, No. 2 August 2022DO - 10.24843/LKJITI.2022.v13.i02.p02, 2022)
One of the popular cryptographic algorithms is the Vigenère Cipher. This algorithm is included in classical cryptographic algorithms, so its capabilities are limited to text-type data. Through this research, this research try to modify the Vigenère Cipher so that it can be used on digital image media. The improvement is performed using ASCII code as a Vigenère table and the key generated by the SHA512 hash technique with salt. The encryption and decryption process was carried out on ten jpg and ten png files and showed a 100% success rate. Speed and memory consumption tests on the encryption process by comparing it with the AES algorithm show that AES excels in speed with 409,467 Mb/s while Vigenère wins in memory consumption by utilizing only 5,0007 Kb for every Kilobytes of the processed digital image file.